(3faMGJ GdhQO GdJhajbis - (3GHf GdedG , EHQGgje Hf CMeO Hf eMeO Hf Ydj Hf GdedG GdMUcaj,J (B1032 (3g` s
(3ChdgG (B:s
(3CMeO Gddg GdPj CeO ef CQGOg hGQJVGg aj cd fajS GdEeOGO s
(3BNQgG (B:s
(3ajchf bhjkG eSJMcekG dGJMdg GdfGQ aVdkG Yf GdWN ceG aj GdOgH s
(3Vef eLehY , JQJjHgG (B: (3GdYGTQs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B30s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs